Zika Virus and Pregnancy: Association between Acute Infection and Microcephaly in Newborns in the State of Rio de Janeiro, Brazil - Pereira, Alessandra Mendelski; Araujo Júnior, Edward; Werner, Heron; Monteiro, Denise Leite Maia (Geburtshilfe und Frauenheilkunde, 2020)
Introduction Aim of the study was to evaluate the association between microcephaly and acute infection with Zika virus (ZIKV) in pregnant women in the state of Rio de Janeiro, Brazil. Infection was confirmed by laboratory testing.Materials and Methods A cross-sectional retrospective study of pregnant women with symptoms occurring between 2015 and 2016 suggestive of acute ZIKV infection was carried out, with confirmation of infection done by blood or urine RT-PCR. The relative proportions of categorical variables were calculated for two distinct groups: pregnant women whose newborns had microcephaly and pregnant women who gave birth to infants without microcephaly. Confidence intervals with a 95% level of agreement were estimated for the relative ratios.Results A total of 1609 pregnant women with a mean age of 26.4 ± 6.5 years were evaluated. As regards the time of acute infection, 19.6% (316) of cases occurred in the first trimester of pregnancy. Nineteen (76%) of the 25 cases with microcephaly (1.5%) were associated with an infection contracted in the first trimester of pregnancy (p < 0.001, OR = 13.7, 95% CI: 5.6 – 37.7). 48% (12/25) of the newborns with microcephaly had a birth weight of < 2500 grams, while only 7% (116/1597) of the group of newborns without microcephaly had a similarly low birth weight (p < 0.001, OR = 11.7, 95% CI: 5.2 – 26.2). Logistic regression showed that a birth weight of < 2500 g (OR = 12.54) and ZIKV infection in the first trimester of pregnancy (OR = 14.05) were associated with microcephaly (area under ROC curve = 0.86).Conclusion Acute ZIKV infection in the first trimester of pregnancy and low birth weight are associated with microcephaly.
Keywords: congenital infection; Zika virus; microcephaly; low birth weight; first trimester of pregnancy